A Novel Iflavirus Was Discovered in Green Rice Leafhopper Nephotettix cincticeps and Its Proliferation Was Inhibited by Infection of Rice Dwarf Virus - Jia, Wenxi; Wang, Fei; Li, Jingjing; Chang, Xuefei; Yang, Yi; Yao, Hongwei; Bao, Yanyuan; Song, Qisheng; Ye, Gongyin (Frontiers in Microbiology, 2021)
The green rice leafhopper, Nephotettix cincticeps (Hemiptera: Cicadellidae), is a key insect vector transmitting rice dwarf virus (RDV) that causes rice dwarf disease. We discovered a novel iflavirus from the transcriptomes of N. cincticeps and named it as Nephotettix cincticeps positive-stranded RNA virus-1 (NcPSRV-1). The viral genome consists of 10,524 nucleotides excluding the poly(A) tail and contains one predicted open reading frame encoding a polyprotein of 3,192 amino acids, flanked by 5’ and 3’ untranslated regions. NcPSRV-1 has a typical iflavirus genome arrangement and is clustered with the members of the family Iflaviridae in the phylogenetic analysis. NcPSRV-1 was detected in all tested tissues and life stages of N. cincticeps and could be transmitted horizontally and vertically. Moreover, NcPSRV-1 had high prevalence in the laboratory populations and was widely spread in field populations of N. cincticeps. NcPSRV-1 could also infect the two-striped leafhopper, N. apicalis, at a 3.33% infection rate, but was absent in the zigzag leafhopper, Recilia dorsalis, and rice Oryza sativa variety TN1. The infection of RDV altered the viral load and infection rate of NcPSRV-1 in N. cincticeps, for which it seems that RDV has an antagonistic effect on NcPSRV-1 infection in the host.